Case Report pada Ibu Hamil dengan Obesitas dan Jarak Anak Terlalu Dekat di Puskesmas Ngrambe - Manggar Arum A.P; Tinuk Esti Handayani; Nurlailis Saadah (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Background: Obesity and a short interpregnancy interval (<24 months) are risk factors that may increase maternal and perinatal complications. Obesity is associated with a higher risk of gestational hypertension, preeclampsia, gestational diabetes, and operative delivery, while a short interpregnancy interval increases the risk of anemia, preterm birth, and low birth weight. The combination of these factors classifies the pregnancy as high risk and requires comprehensive midwifery care. Objective: To describe the implementation of midwifery care for a pregnant woman with obesity and a short interpregnancy interval using a standardized midwifery management approach. Methods: This case report was conducted on Mrs. I, a 25-year-old G2P1A0 woman at 29 weeks of gestation with obesity and an interpregnancy interval of 17 months. Data were collected through interviews, observations, physical examinations, obstetric examinations, and documentation studies. Midwifery care was provided and documented using the SOAP method. Conclusion: The assessment showed a maternal BMI of 32.2 kg/m² and an interpregnancy interval of 17 months. Comprehensive and continuous midwifery care helped maintain favorable maternal and fetal conditions until delivery and improved the mother's readiness to use postpartum contraception.